Experimental factors influencing the bioaccessibility and the oxidative potential of transition metals from welding fumes - Ghanem, Manuella; Alleman, Laurent Y; Rousset, Davy; Perdrix, Esperanza; Coddeville, Patrice (Environmental science--processes & impacts, 2024)
Inhalation of welding fumes (WFs) containing high levels of transition metals (Cr, Cu, Fe, Mn, Ni...) is associated with numerous health effects including oxidative stress. However, the measurements of the oxidative potential (OP) and bioaccessibility of WF transition metals depend on several physicochemical parameters and may be subject to several experimental artifacts. In this work, we investigated the influence of the experimental conditions that may affect the bioaccessibility of transition metals and their OP on stainless-steel WF extracts. WFs were produced using a generation bench and sampled on filters. The soluble fraction of the metals was analysed. Two different extraction fluids mimicking physiological pulmonary conditions were studied: phosphate buffer and Hatch's solution. Three extraction times were tested to determine the optimal time for a significant OP DTT using the dithiothreitol (DTT) method. The storage conditions of WFs after filter sampling such as duration, temperature and atmospheric conditions were investigated. The results indicate that experimental conditions can significantly affect the OP DTT and metal bioaccessibility analyses. Cr, Cu and Ni show higher solubility in Hatch's solution than in the phosphate buffer. Mn is highly sensitive to DTT and shows close solubility in the two fluids. An extraction time of 0.5 h in phosphate buffer allows a better sensitivity to OP DTT , probably by limiting complexations, interactions between metals and precipitation. Storage time and temperature can influence the physical or chemical evolution of the WFs, which can affect their OP DTT and Mn solubility. However, storage under N 2 (g) limits these changes. On-line measurements of OP DTT could provide an alternative to filter sampling to overcome these artifacts. Experimental conditions such as extraction methods and storage conditions induce biases on the measurement of the oxidative potential and the bioaccessibility of transition metals from welding fumes.